Der König und sein Kreis : das staatliche Schatzarchiv der III. Dynastie von Ur - Paoletti, Paola, 1980- (Biblioteca del próximo oriente antiguo ;, 2012)
Southern Mesopotamia, in the city Puzrich-Dagan (currently Drehem) comes from two administrative files from the era of the Ur III Dynasty (s. XXI a.C.) known as the "file of the Treasury" and the "shoes file". The cuneiform tablets of these files document, through the registration of inputs and outputs, the production and administration of property of luxury, for example, jewelry, furniture, weapons and shoes. This book deals with the comprehensive study of these files, it refers to the philological analysis of objects and materials documenting them, both as regards the powerful administrative organization that managed them and the relationship with merchants supplying products, the craftsmen who made them, the officers who supervised transactions, or the personalities of the Clergy or the Royal House to which they were intended.